Thoracic spinal anesthesia with intrathecal sedation for lower back surgery: a retrospective cohort study - Nikolay Boykov; Dilyan Ferdinandov; Dilyan Ferdinandov; Petra Vasileva; Petra Vasileva; Dimo Yankov; Dimo Yankov; Stefan Burev; Rositsa Tanova; Rositsa Tanova (Frontiers in Medicine, 2024)
BackgroundSpinal anesthesia (SA) is a good alternative to general anesthesia (GA) for spine surgery. Despite that, a few case series concern the use of thoracic spinal anesthesia for short-duration surgical interventions. In search of an alternative approach to GA and a better opioid-free modality, we aimed to investigate the safety, feasibility, and patient satisfaction of thoracic SA for spine surgery.Materials and methodsWe analyzed retrospectively a cohort of 24 patients operated on for a degenerative and osteoporotic pathology of the lower thoracic and lumbar spine. Data was collected from medical records, including clinical notes, operative and anesthesia records, and patient questionnaires.ResultsTwenty-one surgeries for herniated discs, two for degenerative spinal stenosis, and one for multi-level osteoporotic vertebral body fractures were performed under spinal anesthesia with intrathecal sedation. In all cases, we applied 0.5% isobaric bupivacaine and the following adjuvants: midazolam, clonidine or dexmedetomidine, and dexamethasone. We boosted the anesthesia with local ropivacaine due to inefficient sensory block in two patients. Nobody in the cohort received intravenous opioids, non-steroidal anti-inflammatory drugs, or additional sedation intraoperatively. Postoperative painkillers were upon the patient’s request. No significant complications were detected.ConclusionThoracic spinal anesthesia incorporating adjuvants such as midazolam, clonidine or dexmedetomidine, and dexamethasone demonstrates not only efficient conditions for spine surgery, a favorable safety profile, high patient satisfaction, and intrathecal sedation but also effective opioid-free pain management.